Bismuth–iron-based precursor: preparation, phase composition, and two methods of thermal treatment. Issue 35 (1st June 2020) - Liu, Yunpeng; Wang, Hao; Qian, Lixiong; Zhao, Xiaoyi; Yao, Lei; Wang, Jiayi; Xing, Xueqing; Mo, Guang; Chen, Zhongjun; Wu, Zhonghua
Abstract : Preparation and phase composition study of bismuth–iron-based precursor, and its thermal treatment by calcination and hydrothermal processes, which can be used to control the synthesis of pure BiFeO3 . Abstract : Bismuth ferrite (BiFeO3 ) is a promising Bi-based perovskite-type material, which is multiferroic due to the coexistence of anti-ferromagnetism and ferroelectricity. During the preparation of pure BiFeO3 nanoparticles, however, the phase structures and species of bismuth–iron-based precursor (BFOH) were still unclear, and so related precursors were prepared. X-ray diffraction, Raman, Fourier transform infrared, and X-ray absorption near-edge structure techniques were used to probe the phase structure and species of the precursors. It was found that the precursor BFOH is composed of Bi6 O6 (NO3 )4 (OH)2 ·2H2 O, Bi6 O5 (NO3 )5 (OH)3 ·3H2 O, Fe(OH)3, and α-Bi2 O3 . Calcination treatment and hydrothermal synthesis were used to prepare the pure BiFeO3 phase from the precursor BFOH. The calcination temperature was optimized as 400 °C for preparation of the pure BiFeO3 phase. Meanwhile, hydrothermal conditions for the synthesis of the pure BiFeO3 phase were also optimized as follows: the reaction solution was the mixture solution of Bi(NO3 )3 ·5H2 O and Fe(NO3 )3 ·9H2 O with cetyltrimethyl ammonium bromide (CTAB) as the surfactant and KOH as the mineralizer; the hydrothermal synthesis was performed at 180 °C for 48 h; the concentration of KOH should be at least 3 M; and the surfactant CTAB can be used to regulate the morphology of the as-prepared BiFeO3 nanoparticles. From the point of view of the microstructure, BiFeO3 nanoparticles prepared by calcination or hydrothermal methods have no notable differences. A formation mechanism from the precursor BFOH to the BiFeO3 product is proposed. By providing an understanding of the precursors, this work is very helpful in the synthesis of bismuth–iron-based nanoparticles.